2020
DOI: 10.21203/rs.3.rs-33438/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Qualitative Study on the Inner Experience of First-Line Nurses in the Clinical Fight against COVID-19

Abstract: Background: With the spread of the Coronavirus Disease 2019 (COVID-19) epidemic in the world, medical staff have become the main force to fight the epidemic. In the process of clinically fighting the epidemic, many nurses experience enormous physical and psychological strain. All parties are under tremendous pressure due to the shortage of medical resources and the large numbers of severely ill patients requiring assistance. Herein, we explored the inner experience of first-line clinical nursing staff during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
6
0
3
Order By: Relevance
“…Our findings are consistent with results observed in other studies, such as Zhang et al, 2020, which found a strong sense of duty and resilience among nurses on COVID-19 units and which also underscored the importance of comradery among nurses, even equating the pandemic to fighting in a war. Meanwhile, as with our work, Lai et al, 2020 found that nurses felt that only other nurses could understand what they were going through.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with results observed in other studies, such as Zhang et al, 2020, which found a strong sense of duty and resilience among nurses on COVID-19 units and which also underscored the importance of comradery among nurses, even equating the pandemic to fighting in a war. Meanwhile, as with our work, Lai et al, 2020 found that nurses felt that only other nurses could understand what they were going through.…”
Section: Discussionsupporting
confidence: 92%
“…Given the drastic potential of the disease, health care professionals who fear they may infect others tend to experience depression, insomnia, anxiety, frustration, anger, and trauma (Barello et al, 2020;Lai et al, 2020;Pappa et al, 2020;Salari et al, 2020;Zhang et al, 2020). Mental and emotional anguish stems from healthcare workers coping with the deaths of colleagues (Maunder et al, 2006), as well as workers' sense of losing control, feeling vulnerable, logging excessive hours, and witnessing the breakdown of social support systems (Chua et al, 2004;Lee et al, 2007;Maunder et al, 2006), all the while managing family responsibilities and other stresses of life issues (Chua et al, 2004;Lai et al, 2020;Maunder et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a systematic literature review of these papers and found only a few studies that specifically addressed nursing staff and COVID-19 (Bird, Badhwar, Fallon, Kwok, & Tang, 2020; Guery et al, 2020; Halcomb et al; Millar, 2020; Mo et al, 2020; Ning et al, 2020; Yifan et al, 2020; H.-j. Zhang et al, 2020; Y.-P. Zhang et al, 2020). Some of these papers described the consequences of COVID-19 in relation to nursing staff (Mo et al, 2020; Ning et al, 2020; H.-j.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 2020; Y.-P. Zhang et al, 2020). Some of these papers described the consequences of COVID-19 in relation to nursing staff (Mo et al, 2020; Ning et al, 2020; H.-j. Zhang et al, 2020; Y.-P. Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%